Method for preparing carbonated nano-gelling active agent through CO2 mineralization as well as product and application of carbonated nano-gelling active agent
The method of preparing carbonated nanogeling active agents through CO2 mineralization solves the problems of low mechanical properties and lack of gel performance in the prior art, and realizes the low carbonization and CO2 resource utilization of high-performance building materials.
Patent Information
- Application Number
- CN202411799771.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the mechanical properties of synthetic calcium carbonate and its composite materials are not high, and lack significant gel performance, making it difficult to apply to the low carbonization of high-performance building materials.
Methods for preparing carbonated nanogeling active agents through CO2 mineralization include calcium source extraction, CO2 absorption, calcium complexation, carbonation and separation and drying processes, using organic acids to complex the calcium ions to induce the formation of amorphous calcium carbonate, thereby realizing the preparation of highly active nanogeling materials.
The prepared carbonated nanogeling active agent has high gelling activity and can be used to synthesize concrete building materials with excellent mechanical strength, realizing resource utilization and efficient CO2 storage.
Smart Images

Figure CN119612990A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic materials, and specifically relates to a method for preparing a carbonation nano-gelling active agent by mineralizing CO2, and a product and application thereof. Background Art
[0002] Carbon dioxide capture, utilization and storage (CCUS) is a large-scale greenhouse gas emission reduction technology that separates carbon dioxide from the atmosphere, industrial or energy-related emission sources or directly utilizes or stores it to achieve carbon dioxide emission reduction or elimination. CCUS technology has broad application prospects and can also be combined with renewable energy technology to form a low-carbon energy system. In the utilization and storage stages, CCUS technology can permanently fix CO2 by combining alkaline earth metals with captured CO2 to form carbonate minerals, while also forming high-value-added carbonate products to generate certain economic benefits.
[0003] The main product of carbon dioxide mineralization of calcium-based materials is calcium carbonate; among them, the main anhydrous crystalline phases are aragonite, aragonite and calcite, among which aragonite and calcite have better thermal stability and are the most common phases. Compared with aragonite and calcite, aragonite is a metastable phase and is easier to transform into other more stable phases. In nature, naturally formed aragonite single phases are rarely found. It can only appear as a by-component in some biominerals, and no aragonite-phase minerals have been found in the geological field. In addition, calcium carbonate has three hydrated phases: monohydrated calcium carbonate, hexahydrated calcium carbonate and amorphous calcium carbonate (ACC). These three phases are very unstable in thermodynamics and often serve as intermediate states of reactions, which can easily transform into other stable phases.
[0004] The instability of the aqueous phase of calcium carbonate makes it very easy to transform into other more thermodynamically stable phases (such as aragonite or calcite). Once this property was discovered, it attracted extensive attention from researchers in the medical, material, chemical and other industries. For example, the Chinese patent document with publication number CN114133208A discloses a stone cultural relic reinforcement and protection material, which is composed of an alcohol solvent and amorphous nano-calcium carbonate dispersed in the alcohol solvent; the stone cultural relic reinforcement and protection material is used to reinforce and protect the cultural relic matrix through the spontaneous transformation of amorphous nano-calcium carbonate to crystalline calcium carbonate. During the hydraulic solidification process, non-stable calcium carbonate undergoes a significant dissolution and recrystallization process, and this process can be used to eliminate the pores between the dispersed particles to form a continuous interface. Therefore, it is expected to prepare calcium carbonate-based gelling active materials with excellent performance using this idea.
[0005] Chinese patent document CN104891547A discloses an amorphous calcium carbonate nanowire material and a preparation method thereof: washing tellurium nanowires to obtain washed tellurium nanowires, wherein the washed tellurium nanowires have a zeta potential of less than or equal to -14 mV; preparing the washed tellurium nanowires into a tellurium nanowire solution, and then mixing the washed tellurium nanowires with an aqueous solution containing a calcium source to obtain a mixed solution, and subjecting the mixed solution to a diffusion reaction with ammonium carbonate crystals to obtain an amorphous calcium carbonate nanowire material. Chinese patent document CN117982661A discloses amorphous calcium carbonate nanoparticles of traditional Chinese medicine and a preparation method thereof: the invention uses a gas diffusion reaction to cause ammonia, carbon dioxide, calcium chloride and a traditional Chinese medicine extract to undergo a mineralization reaction in an organic solvent, and after the reaction, a powder solidified with the traditional Chinese medicine extract is separated, wherein the calcium carbonate of the mineralized powder is amorphous, and the curing rate of the mineralized product to the traditional Chinese medicine extract is greater than 30%. Chinese patent document CN110040757A discloses a method for preparing light calcium carbonate using carbide slag. The invention first removes impurities and other harmful substances in the carbide slag through carbide slag pretreatment, and then couples carbon dioxide captured by industrial carbon with carbide slag suspension to prepare bead-shaped amorphous fine particles of light calcium carbonate.
[0006] It can be seen that there are various methods for synthesizing calcium carbonate and its composite materials in the prior art, and the application of related calcium carbonate synthetic materials is also very extensive. They are often used in the fields of pharmaceuticals, medical device auxiliary materials, personal care, papermaking, etc. However, their mechanical properties are generally not high, and they do not have significant gel properties, and usually require the assistance of other binders. In fact, how to make the CO2 mineralization product calcium carbonate produce stronger gelling properties and apply it to the low carbonization of building materials is still a difficulty in current material development research. Summary of the invention
[0007] In order to solve the shortcomings of the prior art, the present invention provides a method for preparing a carbonated nano-gelling active agent by CO2 mineralization. The process flow is simple, and the prepared carbonated nano-gelling active agent has high gelling activity and can be used to synthesize concrete building materials with excellent mechanical strength, thereby achieving a high level of resource utilization.
[0008] The specific technical solutions adopted are as follows:
[0009] A method for preparing a carbonated nano-gelling active agent by CO2 mineralization, comprising:
[0010] (1) Calcium source extraction: the solid phase calcium source and the extractant are fully mixed to extract calcium ions from the solid phase calcium source into the solution phase, and filtered to obtain a soluble calcium salt solution;
[0011] (2) CO2 absorption: using alkaline absorption liquid to capture CO2 gas and fully dissolve CO2 to form a soluble carbonate solution;
[0012] (3) Calcium complexation: the soluble calcium salt solution of step (1) and an organic acid additive are fully mixed to obtain a complex calcium precursor; the organic acid comprises amino acid, polymerized amino acid or polyacrylic acid;
[0013] (4) Carbonation: Add the soluble carbonate solution of step (2) to the complex calcium precursor. When the mixed system is precipitated and in a colloidal state, terminate the reaction and separate the solid phase in the reaction solution. Wash with a blocking agent and dry to obtain a carbonated nano-gelling active agent.
[0014] The organic acid additive can complex with the calcium ions in the soluble calcium salt, thereby changing the distribution of electrons around the calcium ions, further affecting the crystallization process of the calcium ions and carbonate ions, thereby inducing the formation of nano-sized, highly active amorphous calcium carbonate (i.e., the carbonated nano-gelling active agent). The phase transformation process of the amorphous calcium carbonate can achieve a gelling effect.
[0015] Specifically, the solid calcium source is calcium-containing industrial solid waste or calcium-containing ore. The calcium-containing industrial solid waste includes alkaline solid wastes such as carbide slag, fly ash or magnesium slag. The calcium-containing ore includes alkaline minerals such as wollastonite, basalt or olivine, with a particle size of <100 microns. The extractant is an organic carboxylic acid or an acidic ammonium salt, and the concentration of the extractant is 0.1 to 2 mol / L.
[0016] The extractant includes but is not limited to formic acid, acetic acid, ammonium chloride and the like.
[0017] Preferably, in step (1), the extraction conditions are room temperature and normal pressure, the solid-liquid mass ratio is 1:5-20, and the extraction time is 30-60 min.
[0018] Further preferably, mechanical stirring or magnetic coupling stirring is performed during the extraction process to enhance the extraction efficiency, and the stirring speed is 400 to 1200 rpm.
[0019] Preferably, in step (1), insoluble matter in the extraction solution system is removed by suction filtration.
[0020] In step (2), the purity of CO2 gas is ≥90%. High-purity CO2 gas from CO2 cylinders, liquid CO2 tank trucks, or captured, purified, and compressed gas can be used. Non-high-purity CO2 gas will introduce impurity molecules and affect product quality.
[0021] The alkaline absorption liquid is conducive to the rapid dissolution of CO2 and its recycling, and includes but is not limited to sodium hydroxide solution, potassium hydroxide solution or ammonia water, etc. The concentration of the alkaline absorption liquid is 0.05-1 mol / L.
[0022] In step (2), when the alkaline absorption liquid is used to capture CO2 gas, the preferred CO2 gas flow rate is 100-1000 mL / min and the reaction time is 30 min. Under the above parameters, the reaction is fully carried out and the soluble carbonate is generated.
[0023] Preferably, in step (2), when the CO2 gas is captured by the alkaline absorption liquid, the CO2 gas is sprayed from the bottom of the reactor through a CO2 disperser with a pore size of 0.01-1.0 mm to control the size of the CO2 bubbles to enhance the CO2 absorption efficiency.
[0024] Furthermore, the carbonation process of step (4) is performed after the bicarbonate ions in the soluble carbonate solution are removed.
[0025] The organic acid additive can produce a complex coordination effect with calcium ions, the amino acid is selected from glycine, aspartic acid, etc., and the polymerized amino acid is selected from polyglycine, polyaspartic acid, etc.; the organic acid is further preferably a polymerized amino acid or polyacrylic acid, which has a chain polymerization structure and a large molecular weight, which is conducive to the preparation of the product carbonation nano-gelling active agent.
[0026] Preferably, the amount of organic acid added is 3wt% to 8wt% of the calcium content; the concentration of organic acid is 50 to 500 mg / L.
[0027] Preferably, in step (4), the carbonate ions in the soluble carbonate solution are in excess of the calcium element in the complex calcium precursor in terms of molar ratio. Furthermore, the molar ratio of the calcium element in the complex calcium precursor to the carbonate ions in the soluble carbonate is controlled at 0.7 to 0.9:1, and the reaction time of the mixed system is ≤5 min.
[0028] Preferably, to ensure the solid-liquid separation efficiency, suction filtration and pressure filtration are used for solid-liquid separation, the pore size of the filter membrane is not greater than 10 μm, and the separation time does not exceed 5 min to obtain the solid phase in the reaction liquid.
[0029] After the carbonation reaction in step (4) is completed, amorphous calcium carbonate is obtained. Since amorphous calcium carbonate is active in nature, it will crystallize and denature in a water-containing environment for a long time, so it is necessary to timely block the contact between amorphous calcium carbonate and water. The blocking agent is selected from solvents with low dielectric constants such as methanol, ethanol, acetone, etc., and the number of cleaning times is not less than 2 times.
[0030] Preferably, after washing, freeze drying is performed for not less than 48 hours to remove excess water and blocking agents in the solid phase to obtain the carbonated nano-gelling active agent.
[0031] The present invention also provides a carbonated nano-gelled active agent obtained by the method for preparing a carbonated nano-gelled active agent by CO2 mineralization.
[0032] Specifically, the carbonated nano gelling agent is composed of nanoparticles, and the particle size of the nanoparticles is preferably 30 to 120 nm. The carbonated nano gelling agent has an auxiliary gelling effect.
[0033] The present invention also provides the application of the carbonated nano gelling agent in the field of building materials. After the carbonated nano gelling agent is mixed with cement, etc., it is not necessary to add a binder, but only water to obtain a building material with excellent mechanical properties, which is green and environmentally friendly, and can be used in cement-based materials to achieve auxiliary gelation and enhance their performance, while achieving efficient CO2 storage.
[0034] The present invention also provides a building material, the raw materials of which include the carbonated nano-gelling active agent, cement and water, the mass ratio of the carbonated nano-gelling active agent to the cement is 1:2-10, and the amount of water added is 40%-60% of the dry basis mass; the raw materials are mixed to obtain slurry, and the slurry is formed and cured to obtain the building material.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The method of the present invention can prepare a carbonated nano-gelling active agent under mild conditions of room temperature and normal pressure. The reaction conditions are simple, and the product calcium carbonate has gel properties. It can be used to replace traditional high-energy consumption and high-carbon emission cementitious materials to assist in gelling, improve the performance of cementitious materials, and prepare concrete building materials.
[0037] (2) The present invention provides a new strategy for the resource utilization of industrial solid waste and CO2, which can achieve high-value recovery of industrial solid waste and CO2 while greatly reducing the carbon emissions of the entire life cycle of the preparation of the product carbonation nanogelling active agent, and has great potential in industrial applications.
[0038] (3) The present invention adopts a step-by-step mineralization method, and the extraction, absorption, and mineralization conversion rates are all over 90%. The purity of the prepared carbonated nano-gelling active agent product is higher than 95%. The used extractant mixture and alkaline absorption liquid can be recycled and reused, saving the cost of purchasing raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the process for preparing carbonated nanogel active agents for CO2 mineralization.
[0040] Figure 2 The microscopic morphology of the carbonated nano-gelling active agent in Example 1 is shown in the figure on the left, and the TEM image is shown on the right.
[0041] Figure 3 This is a statistical diagram of the strength of the composite material formed by the carbonated nano-gelling active agent and cement in Example 1. DETAILED DESCRIPTION
[0042] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0043] The schematic flow chart of the method for preparing a carbonated nano-gelling active agent by CO2 mineralization provided by the present invention is as follows Figure 1 As shown, the preparation process includes (1) calcium source extraction, (2) CO2 absorption, (3) calcium complexation, (4) carbonation and (5) separation and drying process. In (1) calcium source extraction, the solid phase calcium source and the extractant undergo extraction reaction, and after the reaction is completed, the filtered soluble calcium salt enters the (3) calcium complexation process; in (2) CO2 absorption, CO2 reacts with the alkaline absorbent to obtain a soluble carbonate and enters the (4) carbonation process; in (3) calcium complexation, a certain amount of organic acid additive is added to the soluble calcium salt to form a complex calcium precursor and enters the (4) carbonation process; in (4) carbonation, the complex calcium precursor and the soluble carbonate undergo carbonation reaction to form an amorphous calcium carbonate product and enter the (5) separation and drying process; in (5) separation and drying process, the carbonation reaction and hydration reaction are stopped by a blocking agent, and after multiple washings and freeze drying, a carbonated nano-gelling active agent with gel properties is obtained.
[0044] Example 1
[0045] In this embodiment, the solid calcium source uses Ca(OH)2 raw material (particle size 20-60 microns) to simulate calcium-containing industrial solid waste or calcium-containing ore, and is added at a calcium ion concentration equivalent to 0.2 mol / L; the extractant uses NH4Cl, and is added at a chloride ion concentration equivalent to 0.4 mol / L; the alkaline absorbent uses ammonia water and is diluted to a concentration of 0.4 mol / L for standby use, CO2 uses 99% concentration cylinder gas; the organic acid additive uses a 500 mg / L polyacrylic acid solution; the blocking agent uses anhydrous ethanol.
[0046] In step (1), Ca(OH)2 and the extractant NH4Cl are fully mixed and stirred to extract calcium ions from the solid phase calcium source into the solution phase. The extraction is continued for 30 minutes at room temperature and normal pressure. The solid-liquid mass ratio during the extraction process is 1:20. After the reaction is completed, the suspension is separated into solid and liquid by a filtration system, and the separated liquid phase is a soluble calcium salt solution containing 0.2 mol / L CaCl2. Specifically, the filtration process uses a filter membrane with a pore size of less than 0.22 μm to ensure that the insoluble solid phase does not enter the soluble calcium salt.
[0047] In step (2), CO2 gas is introduced into an ammonia solution at a flow rate of 100 mL / min for reaction. During the CO2 absorption reaction, the pH value of the solution is monitored. When the pH value drops to around 9.5, the introduction of CO2 gas is stopped. After the reaction is completed, 1-2 mL of ammonia water is added dropwise to remove bicarbonate ions in the system to obtain 0.2 mol / L (NH4)2CO3 soluble carbonate.
[0048] In step (3), the soluble calcium salt solution (0.2 mol / L CaCl2 solution) of step (1) and 500 mg / L polyacrylic acid solution (the amount of organic acid added is 6.25 wt% of the calcium content) are quickly mixed to obtain a colloidal complex calcium precursor.
[0049] In step (4), the soluble carbonate solution (0.2 mol / L (NH4)2CO3) of step (2) is pumped into the complex calcium precursor (the molar ratio of the calcium element in the complex calcium precursor to the carbonate ion in the soluble carbonate is 0.9:1) at a rate of 20 mL / min, the reaction time is 5 min, and the mixed system precipitates and becomes colloidal, thereby obtaining a latex-like calcium carbonate precipitate.
[0050] In step (5), the separation and drying process: the suspension containing the latex-like calcium carbonate precipitate is subjected to solid-liquid separation using a suction filtration system; specifically, the suspension is suction filtered using a filter membrane with a pore size of 0.45 μm, and the suspension is stirred during the suction filtration process to prevent the precipitate from clogging the filter pores. The suction filtration time lasts for about 5 minutes, and the nano amorphous calcium carbonate obtained after the suction filtration is washed twice with anhydrous ethanol blocking agent and then freeze-dried for 48 hours. During the washing process, continuous stirring is required to ensure sufficient blocking. After each washing, the above suction filtration step needs to be repeated to obtain a carbonated nano gelling active agent with stable properties.
[0051] During the above processes of (1) calcium source extraction, (2) CO2 absorption, (3) calcium complexation, and (4) carbonation, a mechanical stirring speed of 800 rpm was used to ensure sufficient reaction.
[0052] like Figure 2 As shown, the obtained carbonated nano-gelled active agent particle size is less than 100 nm.
[0053] Example 2
[0054] The only difference between the present invention and Example 1 is that 95% pure wollastonite (CaSiO3) is used as the solid calcium source, and the other processes and parameters remain unchanged.
[0055] Example 3
[0056] The only difference between the present invention and Example 1 is that polyaspartic acid is used as the organic acid, and the other processes and parameters remain unchanged.
[0057] Example 4
[0058] The carbonated nano-gelling active agent prepared in Example 1 was mixed with cement in a ratio of 1:9, and then 50% of the dry weight of water was added and stirred to obtain a uniform slurry. After the slurry was vibrated to remove the internal bubbles, it was injected into a 50mm×50mm×50mm cubic mold and sealed. After curing for 7 days under natural conditions, the uniaxial compressive strength was 33.9MPa. Figure 3 shown.
[0059] Example 5
[0060] The carbonated nano-gelling active agent prepared in Example 1 was mixed with cement in a ratio of 2:8, and then 50% of the dry weight of water was added and stirred to obtain a uniform slurry. The slurry was vibrated to remove internal bubbles and then injected into a 50mm×50mm×50mm cubic mold for sealing. After curing for 7 days under natural conditions, the uniaxial compressive strength was 35.13MPa. Figure 3 shown.
[0061] Example 6
[0062] The carbonated nano-gelling active agent prepared in Example 1 was mixed with cement in a ratio of 3:7, and then 50% of the dry weight of water was added and stirred to obtain a uniform slurry. After the slurry was vibrated to remove the internal bubbles, it was injected into a 50mm×50mm×50mm cubic mold and sealed. After curing for 7 days under natural conditions, the uniaxial compressive strength was 34.17MPa. Figure 3 shown.
[0063] Comparative Example 1
[0064] Mix PO42.5 cement with 50% dry weight water and stir to obtain a uniform slurry. After vibrating to remove internal bubbles, the slurry is injected into a 50mm×50mm×50mm cubic mold and sealed. After curing for 7 days under natural conditions, the uniaxial compressive strength is 30.25MPa. Figure 3 shown.
[0065] Comparative Example 2
[0066] 2000 mesh calcite calcium carbonate and PO42.5 grade cement were mixed in a ratio of 1:9, and 50% of dry weight of water was added and stirred to obtain a uniform slurry. After the slurry was vibrated to remove internal bubbles, it was injected into a 50mm×50mm×50mm cubic mold and sealed. After curing for 7 days under natural conditions, the uniaxial compressive strength was 29.97MPa. Figure 3 shown.
[0067] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbonated nano-gelling active agent by CO2 mineralization, characterized in that: include: (1) Calcium source extraction: the solid phase calcium source and the extractant are fully mixed to extract calcium ions from the solid phase calcium source into the solution phase, and filtered to obtain a soluble calcium salt solution; (2) CO2 absorption: using alkaline absorption liquid to capture CO2 gas and fully dissolve CO2 to form a soluble carbonate solution; (3) Calcium complexation: the soluble calcium salt solution of step (1) and an organic acid additive are fully mixed to obtain a complex calcium precursor; the organic acid comprises amino acid, polymerized amino acid or polyacrylic acid; (4) Carbonation: Add the soluble carbonate solution of step (2) to the complex calcium precursor. When the mixed system is precipitated and in a colloidal state, terminate the reaction and separate the solid phase in the reaction solution. Wash with a blocking agent and dry to obtain a carbonated nano-gelling active agent.
2. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: The solid calcium source is calcium-containing industrial solid waste or calcium-containing ore, calcium-containing industrial solid waste includes carbide slag, fly ash or magnesium slag, calcium-containing ore includes wollastonite, basalt or olivine, and the particle size of the solid calcium source is <100 microns; and / or, the extractant is selected from organic carboxylic acid or acidic ammonium salt, and the concentration of the extractant is 0.1-2 mol / L.
3. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: The solid-liquid mass ratio during the extraction process is 1:5-20, and the extraction time is 30-60 minutes.
4. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: In step (2), the purity of CO2 gas is ≥90%, the alkaline absorption liquid includes sodium hydroxide solution, potassium hydroxide solution or ammonia water, and the concentration of the alkaline absorption liquid is 0.05-1 mol / L.
5. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: The organic acid is polymerized amino acid or polyacrylic acid, and the amount of the organic acid is 3wt% to 8wt% of the calcium content.
6. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: In step (4), the carbonate ions in the soluble carbonate solution are in excess of the calcium element in the complex calcium precursor in terms of molar ratio, and the reaction time of the mixed system is ≤5 min.
7. The method for preparing a carbonation nano-gelling active agent by CO2 mineralization according to claim 1, characterized in that: The blocking agent is selected from methanol, ethanol or acetone. After washing, freeze drying is performed for no less than 48 hours to remove excess water and blocking agent in the solid phase to obtain the carbonated nano-gelling active agent.
8. A carbonated nano-gelled active agent obtained by the method for preparing a carbonated nano-gelled active agent by CO2 mineralization according to any one of claims 1 to 7.
9. Application of the carbonation nano gelling active agent according to claim 8 in the field of building materials.
10. A building material, characterized in that: The raw materials include the carbonated nano-gelling active agent as claimed in claim 8, cement and water, the mass ratio of the carbonated nano-gelling active agent to cement is 1:2-10, and the amount of water added is 40%-60% of dry basis mass; the raw materials are mixed to obtain slurry, and the slurry is formed and cured to obtain the building material.
Citation Information
Patent Citations
Method for immobilizing carbon dioxide
CN114555212A
Carbonated coal gangue-based paste as well as preparation method and application thereof
CN115108763A
Cited By
Mining cemented filling mortar material for mineralizing and sealing CO2 and preparation method thereof
CN120004565A
Mine-used Cemented Backfilling Mortar Material for Mineralizing and Sealing CO2 and Its Preparation Method
CN120004565B
Amino acid mediated coal-based solid waste negative carbon filling material and preparation method thereof
CN120923173A